The Feasibility of Ultrasonographic Diaphragmatic Excursion in Healthy Dogs: Effect of Positioning, Diaphragmatic Location, and Body Weight of Dogs - Saisawart, Phasamon; Sutthigran, Somchin; Soontornvipart, Kumpanart; Thanaboonnipat, Chutimon; Darawiroj, Damri; Choisunirachon, Nan (Frontiers in Veterinary Science, 2021)
Diaphragmatic excursion (DE) has been utilized for detecting respiratory related problems in humans. However, several factors should be considered such as the ultrasound technique and factors intrinsic to patients. Nevertheless, knowledge of the effect of these factors on DE in dogs is still lacking. The aim of this study was to evaluate the proper ultrasound technique by varying postures and diaphragmatic locations for DE measurement and to explore intrinsic factors such as diaphragmatic sides, sex, and body weight of dogs on DE. Prospective, analytic cross-sectional study include forty-four healthy dogs; 12 beagles and 32 dogs of other breeds. The experiment was divided into (i) an exploration of the proper ultrasound technique by varying postures (supine, standing, and recumbent of in each of the right and left lateral positions), diaphragmatic locations (middle crus and proximal to the last rib) and diaphragmatic sublocations (xiphoid, mid, and proximal rib) for detection of DE and (ii) the evaluation of canine intrinsic factors affecting DE. The result show that the mid diaphragmatic sublocation in the middle crus area in almost all positions revealed the highest percent DE detection. However, DEs were revealed to be more accessible in the supine position. There was no significant difference in DE between the right and the left diaphragms or between the sexes of beagle dogs. However, body weight was significantly correlated with the DE among dogs of various sizes. In conclusion, the posture of the dogs and the diaphragmatic location can affect DE evaluation. Neither sex nor diaphragmatic side had an influence, but body weight was revealed as a major factor in DE in dogs.